PERSEPSI GURU PAMONG TERHADAP KOMPETENSI PEDAGOGIK MAHASISWA PPL PENDIDIKAN EKONOMI DI SMA ISLAMIYAH PONTIANAK - yarso, Maimuna; Warneri, Warneri; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the Competenence of Pedagogical Student Education Economics that Implement PPL in SMA Islamiyah Pontianak. The research metodh used is deskriptive with the research from of Study Survey. The data source of this research is 2 Tutor Teachers of Economics Education and the data is Perceptions of Tutor Teacher on Pedagogical Competence of Economics Education Students as well as interwiew with Tutor Teacher Economics Education Students. Based on the results of the research shows 1)Student Ability in Understanding of Students in the good category, 2)Student Ability in Learning Planning in the good category, 3)Student Ability in Implementation of Learning in the very good category, 4)Student Ability in Evaluation of Learning Outcomes in the sufficient category, 5)Student Ability in Potential Development of Students in the sufficient category. Thus, it can concluded that the Pedagogical Competence of FKIP UNTAN Economic Education Students who implement PPL in SMA Islamiyah Pontianak according to Perceptions of Tutor Teacher in the category Good.Â Keywords: Pedagogical Competence, PPL Student, Teacherâ€™s PerceptionÂ